The dams and water management systems of Minoan Pseira - Betancourt, Philip P. (INSTAP Academic Press, 2012)
Excavations at the Bronze Age seaport on Pseira Island uncovered the remains of sophisticated water retention systems that included the addition of retaining walls to prevent erosion, massive dams with associated reservoirs, and small check-dams to ravines that reached over one hundred meters in length in order to control water runoff and make it available for human use. Agriculture was one of the cornerstones of the Bronze Age Cretan economy, and it is no surprise that the ancient inhabitants of the island went to great lengths to control water runoff and make it available for human use. Desp